Leading Authentically: Overcoming the Mind-Boggling Consequences of Mindless Leadership - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2015)
The extent of fake leadership and management behaviour in business and society is mind-boggling as indicated by the large number of corporate non-compliance cases and trust violations. Examples include the BP Deepwater Horizon oil spill, the damaged reputation of UK-based pharmaceuticals giant GlaxoSmithKline as a consequence of a bribery case in China or the recent class action lawsuit related to price-fixing of tickets for trans-Pacific flights.